THE EFFECT OF EXTERNAL RADIOTHERAPY TO THE LEFT VENTRICLE SYSTOLIC FUNCTION IN LOCALLY ADVANCED BREAST CANCER PATIENTS, ANDHRA PRADESH, INDIA: A COHORT STUDY. - Medida, John Winkle; Amarthaluri, Satish Kumar; P Madhuri; Uppala, Pradeep (Student’s Journal of Health Research Africa, 2024)
Introduction: People having cancer on the left side are more prone to develop cardiac issues than patients with other-sided malignancies, and radiation therapy (RT) has certain risks. This study aims to offer a dosimetric analysis of how radiation therapy (RT) affects the heart and coronary arteries following breast conservation surgery and to ascertain whether these dosages are linked with a greater risk of ischemic heart disease (IHD). Methods: A random selection of 150 patients with early-stage T1/T2 + N0 breast carcinomas was made on both the left and right sides. In these individuals, the entire breast was treated with radiation, and the tumor beds were expanded and planned to use computed tomography. The dosages for the left ventricle (LV), right ventricular (RV), left anterior descending coronary artery (LAD), and left circumflex coronary artery (LCx) were noted. Results: The mean dose to the left anterior descending coronary artery (LAD) for left-sided breast cancer patients was significantly higher at 2402.480 ± 838.40 cGy compared to right-sided patients. The left ventricle (LV) in left-sided patients received an average dose of 397.56 ± 131.73 cGy, while the right ventricle in right-sided patients received 130.18 ± 24.92 cGy. High doses in cardiac substructures were noted for left-sided patients, with significantly elevated Dmean, Dmin, and Dmax values for the LCx, LAD, RV, and LV (P < 0.0001). This increased radiation exposure is associated with a higher risk of developing ischemic heart disease (IHD) in left-sided breast cancer patients. Conclusion: The most straightforward and effective way to lessen and prevent radiation-induced cardiac harm, particularly in cases of left-sided breast cancer, is to balance dosage limits between the mean heart dose and many high-dose zones of cardiac substructures. Recommendation: After a certain age, it is advising routine breast screening to lower breast cancer risk.